2016
DOI: 10.1007/s00432-016-2116-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of CD44 surface expression in advanced stage serous epithelial ovarian cancer: a prospective study

Abstract: CD44 expression contributes to the development of carboplatin resistance in advanced serous EOC, and it may contribute to worse prognoses for patients, but it is neither an independent predictor of survival nor of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…We found five and seven ovarian cancer cell lines to be CD24- and CD44-positive, respectively ( Table I ). In some studies, CD44 expression has been associated with epithelial to mesenchymal transition and shorter disease-free and overall survival in patients with ovarian cancer ( 67 , 68 ). In this study, we found that treatment of SKOV3 cells with both afatinib and erlotinib was accompanied by the downregulation of CD44 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We found five and seven ovarian cancer cell lines to be CD24- and CD44-positive, respectively ( Table I ). In some studies, CD44 expression has been associated with epithelial to mesenchymal transition and shorter disease-free and overall survival in patients with ovarian cancer ( 67 , 68 ). In this study, we found that treatment of SKOV3 cells with both afatinib and erlotinib was accompanied by the downregulation of CD44 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CD44 is the hyaluronate receptor and is important in adhesion. In ovarian cancer CD44 correlates with chemoresistance and tumor progression [74][75][76] . One function of CD44 is to activate Stat3 77 .…”
Section: Cell Surface Markersmentioning
confidence: 99%
“…Positive CD44 expression was demonstrated to be a prognostic indicator of shorter survival time in patients with ovarian cancer (4-7). CD44 expression was also reported to contribute to the development of carboplatin resistance in advanced serous epithelial ovarian cancer, and contribute to a worse prognosis for these patients (7). In addition, epithelial cadherin (E-cadherin) is a calcium-dependent cell-cell adhesion glycoprotein.…”
Section: Introductionmentioning
confidence: 99%